Understanding and shaping spatial transformation processes through transdisciplinary case studies - Moritz Engbers (Spatial transformation: Processes, strategies, research design, 2022)
A transdisciplinary case study focuses on a particular phenomenon in its social, cultural, economic and ecological context. Transdisciplinary means, first of all, that people from different fields - such as science, administration, art or business - conduct research together on socially relevant problems, learn from each other and develop interventions. Cases can be understood as boundary objects, which allow participants' perspectives to be identified and discussed. An approach to transdisciplinary research that is sensitive to differences can help to better understand and shape spatial transformation processes. In-between spaces that exist between disciplines, sectors, fields of work and living environments offer the potential to examine spatial processes from different perspectives and to question what is usually taken for granted as well as non-sustainable ways of thinking and acting. The conceptual contributions are illustrated using examples from a transdisciplinary case study in the district of Oldenburg with actors from science, art, the regional administration and civil society.
urn:nbn:de:0156-08911689; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Difference; transformative research; sustainability; in-between spaces; experimenting and reflecting